Two fine ladies have a tiff - Zehler, Antonia (New York : Random House, 2001)
Two refined lady friends have a very unrefined disagreement.
Accelerated Reader AR
Keywords: Friendship -- Juvenile fiction; Conflict management -- Juvenile fiction; Conduct of life -- Juvenile fiction; Friendship -- Fiction; Conflict management -- Fiction; Conduct of life -- Fiction